Financing Small and Medium Enterprises in Bangladesh – Issues and Challenges - Hasan, Fuad; Jamil, Gazi Mohammad Hasan (The Asian Journal of Technology Management (AJTM), 2014)
Abstract. Now-a-days, Small and Medium Enterprises (SMEs) have become an important sector that is supposed to play a pivotal role in boosting the economy of Bangladesh. But, SME financing is still facing some remarkable challenges that limit its potential success in contributing to the economy. Lots of thinking has contributed to the initiation and development of SMEs in Bangladesh. Now is the time to identify the challenges and making adjustments to the initial thinking. This paper is, therefore, an attempt to analyze various issues and challenges of financing this particular sector and find some worthy ways out to overcome these challenges. It will also survey various literatures and reports on the concerned field and recommend supporting actions to help this highly prospective industrial sector operate in a fully yielding manner.Keywords: SME, Financing, Development, Bangladesh economy, Industrial sector